Peran Mahasiswa KKN dalam bidang Pendidikan berbasis Teknologi (Sebuah Studi Kasus terhadap Warga Masyarakat Desa Sumberjaya, Kecamatan Tempuran, Kabupaten Karawang) - Salwa Hanya Dwi Putri (Peneliti.net, 2023)
Digital literacy is the ability to obtain, understand and use information from various sources in digital form (Gilster, 1997). This article examines various processes of training activities in order to implement the use of android applications for teaching and learning activities. This article uses descriptive analysis method, descriptive analysis is a type of research that has the aim of describing the character of a variable, group or social phenomenon that occurs in society, without making comparisons, or connecting with other variables (Sugiyono, 2010). The sampling method uses interviews and an in-depth approach. The results of this training show that the digital literacy process among elementary school’s teachers in Sumberjaya village is quite sufficient in digital literacy competence.